The Effect of Gender Inequality in Employment on Economic Growth in Batam City - M Rizki Aula; Yudhanto Satyagraha Adiputra (Jurnal Ilmu Sosial dan Humaniora, 2024)
This study aims to examine the effect of gender inequality in employment on economic growth in Batam City. The associative quantitative research method is used with multiple linear regression analysis techniques to describe the relationship between variables in the study. The results show that simultaneously, labor force participation rate (LFPR), wage equality, and work progress have an influence on economic growth, where any reduction in gender inequality in employment contributes to boosting economic growth. Therefore, a collaboration between the government, private sector, and non-governmental organizations is expected to encourage the implementation of gender mainstreaming policies and programs that support gender equality in the employment sector and have the potential to make a positive contribution to economic growth.